Modelling of knowledge and attitudes as key determinants of Mpox prevention practices among university students in Ghana: a cross-sectional analysis - Napoleon Bellua Sam; Nuhu Abdul-Aziz Yembedara; Adams Dramani (New Microbes and New Infections, 2025)
Introduction: Mpox has surfaced as a primary health problem since the global outbreak in 2022. This study sought to evaluate and also use structural equation modelling (SEM) to predict the knowledge, attitudes, and preventive practices concerning Mpox among students. Methods: A descriptive cross-sectional survey was conducted with 469 students at the University for Development Studies. Data were collected using a structured questionnaire with SEM and cumulative percentage employed to analyze and predict both knowledge and attitudes on preventive practices among university students. Results: A significant majority (84.2 %) correctly identified Mpox as an infectious disease caused by the Mpox virus, though 55.0 % incorrectly believed it to be the same as smallpox. The overall knowledge of Mpox among university students was poor (59.1 %), with 40.9 % demonstrating either acceptable (32.4 %) or excellent (8.5 %) levels of knowledge. Despite this, 77 % of students had a favorable attitude towards the disease. Preventive practices were predominantly excellent, with 78.7 % of students exhibiting excellent practices, while only 3.8 % demonstrated poor practices. SEM revealed a positive, statistically significant association between knowledge (β = 0.23, P < 0.001), attitude (β = 0.38, P < 0.001), and preventive practices. Additionally, a strong positive effect was found between knowledge and attitudes towards Mpox (β = 0.50, P < 0.001). Conclusion: The study emphasizes that although students have limited knowledge about Mpox, their positive attitudes greatly aid in the implementation of successful preventive measures. Improving knowledge may result in even better preventive actions, highlighting the necessity of focused educational programmes to raise students' knowledge of Mpox.